The thermal and dynamical state of the Antarctic mesopause region during winter/summer transition and the role of stratosphere/mesosphere coupling - Lübken, Franz-Jospeh; Höffner, J.; Viehl, T. P.; Latteck, R.; Becker, Erich; Kaifler, Bernd; Murphy, Damian J.; Morris, R. J. (2015)
The transition of stratospheric circulation at Antarctic latitudes from winter to summer conditions is highly variably from year to year. As has been realized recently, this also affects the winter/summer transition at mesopause altitudes. The Antarctic middle atmosphere therefore offers the unique possibility to study the physical processes involved in the vertical coupling between the stratosphere and the mesosphere during winter/summer transition, in particular the role of gravity waves. We present new results from the mobile scanning iron lidar of the Leibniz Institute of Atmospheric Physics in Kühlungsborn (IAP) which was in operation at Davis, Antarctica, from December 15, 2010, until December 31, 2012. It measured temperatures in the iron layer (~80-100 km). The lidar can operate under daylight conditions. At Davis, the lidar has achieved at total of 2900 hours of temperature measurements which is presumably the largest nearly continuous data set in Antarctica. In this presentation we concentrate on the winter/summer transition and compare with circulation changes in the stratosphere derived from MERRA. We also compare with the northern hemisphere (NH). The thermal structure around the mesopause at Davis is closely coupled to the general circulation in the stratosphere, more precisely to the transition from winter to summer conditions. In contrast to theoretical expectations we occasionally find the mesopause significantly higher and colder(!) compared to the NH. The mesopause altitude changes by several kilometers throughout the summer season, which is significantly different from the summer in the northern hemispheric. Depending on altitude, temperatures can be warmer or colder compared to the NH summer. We studied the seasonal variation of polar mesosphere summer echoes (PMSE). PMSE are strong radar echoes related to ice particles and therefore require very low atmospheric temperatures. The VHF radar frequently detected PMSE. We compare the seasonal variation of PMSE with stratospheric circulation, ...